SENSITIVITAS DAN SPESIFISITAS TES ANTIGEN FESES DALAM MENDIAGNOSIS INFEKSI HELICOBACTER PYLORI PADA PASIEN DENGAN ULKUS PEPTIKUM DISERTAI PERDARAHAN - Prasetyo, Dimas Seto; Nathan, Johan (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Background: The aim of this study was to determine the sensitivity and specificity of the stool antigen test in diagnosing Helicobacter pylori infection in patients with peptic ulcers accompanied by bleeding. Method: This was an evidence-based case report. A literature search was carried out on five databases (MEDLINE, Cochrane Library, Scopus, ScienceDirect, Embase). The search was carried out using the keywords: H. pylori, peptic ulcer, stool antigen test, culture, histology, and biopsy without using language filters, study design, or year of publication according to eligibility criteria. Critical review and level of evidence determination were carried out using critical appraisal tools from CEBM Oxford University. Results: A total of 215 articles were obtained from the search results. After screening abstracts, titles, and removing duplicate articles, 23 full-text articles were obtained. In the full-text review, 16 articles were excluded because the subjects did not meet the inclusion criteria and 1 article had a different outcome. In this EBCR, there was 1 SR-MA article from 6 cross-sectional studies with sensitivity results of 87% (82-91) and specificity of 70% (62-78). However, these studies have a high level of heterogeneity. Most studies on EBCR show poor specificity of the stool antigen test (52%-68%). The high number of false positive results from several studies could be due to cross-reaction of blood with H. pylori antigens. Conclusion: The stool antigen test can be considered as an additional diagnostic test in patients with peptic ulcers accompanied by bleeding if the patient has contraindications to invasive diagnostic tests.